The Effect of the Work Environment on Work Productivity in PT. Intercontinental Transport Express - Amanda Pratiwi; Kifni Yudianto (Formosa Journal of Science and Technology, 2023)
The research aims to determine how much influence the environment has on work productivity at PT Ekspres Transportasi Antarbenua. This research is a quantitative research. The population includes employees who work at PT Ekspres Transportasi Antarbenua and a sample of 32 respondents. The data analysis technique uses simple regression analysis which is processed using SPSS (Statistical Product and Service Solutions) For Windows release 26.0. The results of the study prove that there is a significant influence between the work environment on work productivity at PT Ekspres Transportasi Antarbenua. The t test results prove 0.000 <0.05, which means the significant value is less than 0.05. The results of the coefficient of determination R2 is 0.462 which can be concluded that the work environment affects work productivity by 46.2% while the remaining 53.8% is influenced by other variables not discussed in this study.